Recurrent Heatwaves Slow Down the Recovery of a Phytoplankton Community - Francesco Polazzo; Markus Hermann; Melina Crettaz‐Minaglia; Andreu Rico (Ecology and Evolution, 2024)
ABSTRACT Heatwaves (HWs) are predicted to increase in frequency and severity due to climate change. Yet, there is limited information about how ecological resilience of aquatic communities is going to be impacted by recurrent HWs. Here, we used data from an outdoor freshwater mesocosm experiment where a semi‐natural phytoplankton community was exposed to three subsequent HWs. The data were used to test two different hypotheses regarding community and ecosystem responses to recurrent perturbations: critical slowing down and rescue. Slowing down would determine a reduction in resilience and eventually a community or ecosystem collapse, whereas rescue would increase community or ecosystem resilience and maintain stable community and ecosystem properties. The results of our experiment showed evidence for critical slowing down, but not for community or ecosystem rescue. The recovery capacity of phytoplankton biomass and dissolved oxygen gradually decreased after the first two HWs and sharply declined after the third one. The decline in these community and ecosystem properties were linked to a significant compositional turnover in the phytoplankton community. Although we did not find evidence for a transition into an alternative stable state, our results provide insights into how the overall resilience of a phytoplankton community may decline in the presence of recurrent heatwaves. Thus, we highlight the importance of monitoring the slowing down of recovery of aquatic communities experiencing repeated exposure to severe perturbations.